Improving football playing skills through teaching games for understanding: A small-sided games approach - Firmana, Iif; Subarjah, Herman; Mahendra, Agus; Nuryadi, Nuryadi; Sofyan, Davi (Journal Sport Area, 2023)
Teachers may find difficulty to design assignments that will increase arousal and keep students’ attention during stages that will encourage them critically to reflect on their actions during physical education activities. Designing assignments that increase arousal and maintain students' attention during physical education activities can be a challenging for teachers, often resulting in a reliance on traditional skills-based approaches. This study aims to address this issue by applying the Teaching Games for Understanding (TGfU) model with a small-sided games (SSG) approach to enhance students' football playing skills. The study used 3 vs 3 invasion games to evaluate playing skills, with a game performance evaluation tool (GPET) used as the playing skill instrument. Decisions regarding coding and execution are made in accordance with the subject of the tactical challenge to be solved, including on- and off-ball attackers. The findings revealed that the experimental group’s decision-making ability when passing was 7.97 and when dribbling was 7.28. The performance results in the experimental group were 7.98 and those in the control group were 7.48. The research made a valuable contribution by demonstrating how using TGfU and SSGs can improve football skills and enhance the quality of teaching in physical education. One limitation is that the research only focused on football playing skills, so the results may not be generalizable to other sports or activities. Future research can investigate the impact of the intervention on other outcomes, such as enjoyment, motivation, and participation in physical activity.